Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kemampuan Pengelolaan Kurikulum oleh Tenaga Pendidik di SMKN 1 Bandung Tulungagung - Dini Syari’ah; Binti Maunah (Mataram University, 2026)
Principal leadership is a crucial factor determining educational success, but the phenomenon of authoritarian leadership cases indicates a gap between formal roles and effectiveness in the field, especially in relation to curriculum management. This study aims to examine in depth the leadership style of the Principal at SMK Negeri 1 Bandung Tulungagung and its implications for improving the curriculum management capabilities of educators. This study also aims to identify the leadership style and describe the curriculum management carried out by educators. This study adopted a qualitative approach with a focused case study type, where the researcher acted as the main instrument at the research site. Primary data sources involved the Principal, the Vice Principal for Curriculum, and educators. Data were collected using triangulation techniques (participant observation, in-depth interviews, and documentation studies) and analyzed interactively using the Miles and Huberman model. The results of the study confirm that leadership effectiveness lies in an adaptive and multifaceted approach that simultaneously integrates the roles of educator, leader, manager, motivator, administrator, innovator, and supervisor. The principal implemented instrument differentiation: transactional aspects (rewards and punishments) were directed at managing behavior and discipline directly tied to curriculum implementation, while transformational aspects (training/internships) were directed at improving technical competency. This success was supported by the supervisor's role through classroom visits that ensured the internalization of new knowledge into actual practice. This finding is significant because it offers a validated applied model for vocational school management, demonstrating that the effectiveness of curriculum management depends on the flexibility and comprehensiveness of the leader's managerial role.